2022
DOI: 10.1111/imr.13081
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin/secreted phosphoprotein‐1 harnesses glial‐, immune‐, and neuronal cell ligand‐receptor interactions to sense and regulate acute and chronic neuroinflammation

Abstract: Our understanding that brain microglia display diversity in gene expression depending on developmental age, region, and in the context of health and disease has rapidly increased over the last several years. The advances emerge from the insights of genetic and molecular tools, which permit interrogation at the single-cell level.Microglia are the innate immune cell guardians of the central nervous system responding to infection, injury, or any chronic condition that disrupts normal homeostatic functions. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 167 publications
1
44
0
Order By: Relevance
“…In examining the DEGs, we were particularly intrigued by the increase in SPP1 (also known as osteopontin), a pleiotropic molecule produced by, and with numerous effects on, macrophage and microglia, as well as with links to neurodegenerative disorders and many other diseases ( 98 , 103 – 107 ). Its expression was significantly increased in all microglia clusters, but not in the macrophage cluster ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In examining the DEGs, we were particularly intrigued by the increase in SPP1 (also known as osteopontin), a pleiotropic molecule produced by, and with numerous effects on, macrophage and microglia, as well as with links to neurodegenerative disorders and many other diseases ( 98 , 103 – 107 ). Its expression was significantly increased in all microglia clusters, but not in the macrophage cluster ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…One specific immune molecule that has recently garnered significant interest as a potential therapeutic target and biomarker for CNS diseases is Osteopontin. This was the focus of the article contributed by Dr. Brown and colleagues in this special issue 18 . Here, they highlighted the fascinating biochemistry of this multifunctional protein and discussed current evidence of its involvement in multiple brain conditions including CNS injury, NeuroHIV infection, and stroke, just to name a few.…”
Section: Figurementioning
confidence: 99%
“…This was the focus of the article contributed by Dr. Brown and colleagues in this special issue. 18 Here, they highlighted the fascinating biochemistry of this multifunctional protein and discussed current evidence of its involvement in multiple brain conditions including CNS injury, NeuroHIV infection, and stroke, just to name a few. Overall, they provide a persuasive argument as to why Osteopontin is an especially attractive therapeutic target for a spectrum of neurological disorders.…”
mentioning
confidence: 99%
“…In addition to SCI, repetitive mild TBI (rmTBI) not only triggered neuroinflammation but may also have led to long-term neurodegenerative diseases like AD [ 171 ]. Microglia, as specific resident macrophages in the CNS, play key roles in the development and regression of neuroinflammation [ 172 , 173 ]. One study [ 75 ] reported that intravenous administration of microglia exosomes harboring miR-124-3p could target neurons and alleviate neurodegeneration.…”
Section: Research and Applications Of Exosomal Drug Delivery Systems ...mentioning
confidence: 99%